Geochemistry on sediment and nodules from the Madeira Abyssal Plain - Ebbing, J; van der Borg, Klaas; de Jong, Arie F M; Nederlof, H P (Supplement to: Ebbing, J et al. (1991): Continuous surface dwelling of manganese nodules on a hill on the Madeira Abyssal Plain during abrupt sedimentation changes. Marine Geology, 98(1), 73-82, https://doi.org/10.1016/0025-3227(91)90036-4, 1991)
The accretion rate of manganese nodules and the sedimentation rate of the underlying sediment has been studied with 10Be and 14C on a nodule covered hill in the Madeira Abyssal Plain. The accretion rate of (3.2 +/- 0.6) mm/Ma for the nodules is considerably smaller than the average sedimentation rate of 12 mm/ka for the last 50-100 ka. The mechanism that kept the nodules at the surface in this specific environment during the last 40 ka is likely to be flotation. The discovery of a large manganese-covered concretion in a piston core points to a long period of sediment winnowing. The 14C analyses also seem to point to an increase in the sedimentation rate round 6500 yrs B.P.